Development of Contextual Learning Design Based on Newman's Diagnosis in Junior High School Fraction Material - Via Arik Kusuma; Nawal Ika Susanti (Divisi Penelitian Yayasan Simfoni Ilmu Cendekia, 2026)
The digital era demands strong mathematical literacy, yet students often encounter significant obstacles with fractions, particularly in word problems. This study aimed to develop a contextual learning design integrating the Newman Diagnosis to analyze and enhance the mathematical literacy of female junior high school students regarding fraction operations. Employing the Research and Development (R&D) method based on the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the study involved 34 seventh-grade female students from SMP Plus Darussalam. Data collection involved preliminary observation, expert validation, pre-tests, post-tests, and an analysis of error patterns using the Newman model. The results demonstrated that the learning design—comprising a teaching module and Student Activity Sheets (LAS) structured according to the Newman framework—possessed very high validity (validation scores ranging from 81.82% to 90.91%). Implementation of the product proved effective in significantly improving mathematical literacy, evidenced by an increase in the mean score from 18.03 (pre-test) to 37.56 (post-test) and a moderate N-Gain category across all literacy indicators. Error analysis revealed that the students' errors were concentrated primarily in the Transformation (47.45%) and Process Skills (46.86%) stages, while error rates in the Reading (17.25%) and Comprehension (17.25%) stages were comparatively low. It is concluded that integrating Contextual Teaching and Learning (CTL) with the Newman Diagnosis successfully addressed systematic conceptual barriers, established a coherent problem-solving flow, and tangibly fostered students' mathematical literacy regarding fractions.